2016
DOI: 10.1103/physrevlett.116.031101
|View full text |Cite
|
Sign up to set email alerts
|

Testing General Relativity with the Shadow Size of SgrA*

Abstract: In general relativity, the angular radius of the shadow of a black hole is primarily determined by its mass-to-distance ratio and depends only weakly on its spin and inclination. If general relativity is violated, however, the shadow size may also depend strongly on parametric deviations from the Kerr metric. Based on a reconstructed image of Sagittarius A * (Sgr A * ) from a simulated one-day observing run of a seven-station Event Horizon Telescope (EHT) array, we employ a Markov chain Monte Carlo algorithm t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
152
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 58 publications
0
152
0
Order By: Relevance
“…It is probable that an algorithm (see e.g. [43,45]) trying to detect a Kerr BH shadow on an image similar to the left panel of Fig. 8 would not converge because there is nowhere in the image a photon-ring-like structure: there is no edge (i.e.…”
Section: Fig 5 Configuration I Images Upper Panel: Image At 230mentioning
confidence: 99%
“…It is probable that an algorithm (see e.g. [43,45]) trying to detect a Kerr BH shadow on an image similar to the left panel of Fig. 8 would not converge because there is nowhere in the image a photon-ring-like structure: there is no edge (i.e.…”
Section: Fig 5 Configuration I Images Upper Panel: Image At 230mentioning
confidence: 99%
“…Ref. 89 used a simulated one-day observing EHT run with seven antennas, and demonstrated that the radius of the shadow of Sgr A* can be measured to an accuracy of ∼1.5 µas (corresponding to 6%). Ref.…”
Section: Shadow Measurement Accuracy and Interferometric Simulationsmentioning
confidence: 99%
“…Other models such as the Kerr black hole with scalar hair predict shadows of distinguishable shape from those in general relativity [14]. Differentiability of shadow characteristic by the EHT between Randall-Sundrum and Einstein-Gauss-Bonnet black holes have also been considered [8]. Perhaps the most compelling result is that for the Modified Gravity black hole [17], which predicts a shadow radius bigger than that of the standard Kerr solution, depending on the (non-universal) size of the Modified Gravity parameter α.…”
Section: Introductionmentioning
confidence: 99%
“…A second test -the imaging of a black hole's "shadow"/photosphere, and by proxy its event horizonis looming near. Pioneered by the Event Horizon Telescope (EHT) and BlackHoleCam consortia [4,5], it will involve targeting the putative supermassive black hole Sagittarius A* (Sgr A*) at the center of the Milky Way [6], as well as active galactic nuclei [7], and it is anticipated that this will provide a crucial test of GR against competing theories by allowing precision measurements of the horizon size [8].…”
Section: Introductionmentioning
confidence: 99%